SICURA: a new handheld radionuclide identification device with gamma and neutron response. (26th July 2021) - Menzio, L.; Lega, A.; Scordo, A.; Capoccia, C.; Ferrante, L.; Bedogni, R.; Curceanu, C.
Abstract: SICURA is a two-year project that aims to develop a portable device to be employed in the prevention of illicit trafficking of radioactive material through γ and neutron detection. In order to be attractive to industries, efforts were made to fulfill the following characteristics: portability, good photon energy resolution and sensitivity in compliance with relevant international standards, sensitivity to neutrons with energies typical of the most common sources, fast response, low cost, user friendly interface. The SICURA system consists of two photon detectors for photon detection (CsI) and spectrometry (CZT) and a moderated Helium-3 counter for neutron detection. Dedicated analog and digital electronics readout have been developed, ensuring high energy resolution for accurate elements identification, signal digitization, alarm and information transmission to the end user. This paper describes the development of the SICURA device and the first results of its individual detectors characterizations.